1956
DOI: 10.1021/ie50564a026
|View full text |Cite
|
Sign up to set email alerts
|

Poly-alpha-methylstyrene

Abstract: Fddeiis \* ird scine Rcldxation mil cincr rcgistrierenden Melibrucke gemessen.Durdi die dynamische Belastung wird ein Endwert der Spann u n g bei Rclaxation vie1 schneller erreicht als im statischen Fdllc. Statis& wurde nach 14 h noch kein Endwert gefunden, bei tlyndniischcr Belastung und gleicher Dehnung (25 Hz mit 1,2 mm Amplitude bei 10 bis 40°/o Dehnung der 100 mm langen Proben) uurdc dieser inncrhalb einer Stunde erreicht und anderte sich iiber 13 weitere Stunden nicht. Im dynamischen Falle findet die Rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1958
1958
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…The properties of PαMS might be somewhat unique compared to other, more studied, polymers because the methyl group in PαMS results higher density and stiffness than, e.g., for PS. 64 Also, it has been reported that T g decreases in supported thin PαMS films with reductions of ∼15 °C for 20 nm thickness films. 65 This is somewhat less than the reductions observed for PS.…”
Section: ■ Discussionmentioning
confidence: 96%
“…The properties of PαMS might be somewhat unique compared to other, more studied, polymers because the methyl group in PαMS results higher density and stiffness than, e.g., for PS. 64 Also, it has been reported that T g decreases in supported thin PαMS films with reductions of ∼15 °C for 20 nm thickness films. 65 This is somewhat less than the reductions observed for PS.…”
Section: ■ Discussionmentioning
confidence: 96%
“…PαMS is an amorphous polymer with outstanding hardness, heat resistance and solvent resistance properties [187]. While PαMS in general finds good solubility in both aromatic and halogenated solvents, only PαMS with a low molecular weight can be soluble in methyl ethyl…”
Section: Poly(α-methylstyrene) With Varying Molecular Weightmentioning
confidence: 99%
“…PαMS is an amorphous polymer with outstanding hardness, heat resistance and solvent resistance properties. 187 While PαMS in general finds good solubility in both aromatic and halogenated solvents, only PαMS with a low molecular weight can be soluble in methyl ethyl ketone. The physical properties of PαMS such as solvent resistance depend on the amount of monomer and low molecular weight polymer in the compositions.…”
Section: Overview Of Polymers With Varying Molecular Weightsmentioning
confidence: 99%
“…Methyl vinyl ketone belongs in this group (707), and apparently alpha-methylstyrene does also. Cationic homopolymerization has been most used with alpha-methylstyrene, but polymerization using sodium was developed by Jones (77,78,65,66). The monomer gave polymers of moderate molecular weight by heating under high pressure (704), and solid polymers can be obtained by slow photopolymerization at room temperature (707).…”
Section: Characteristics Of Ionic Polymerizationsmentioning
confidence: 99%